Catastrophes and complicated intraoperative events during robotic lung resection - Louie, Brian E. (Journal of Visualized Surgery, 2017)
Intraoperative complications and catastrophes are an accepted and perhaps inevitable aspect of all surgeries. Anatomic pulmonary resection puts in close proximity the tracheal-bronchial tree, pulmonary vasculature, heart and great vessels within the small volume area of the chest. Fortunately, major complications and catastrophes are uncommon regardless of surgical approach. Pulmonary arterial injury is the most frequently reported. Most injuries necessitate a thoracotomy for definitive management though novel techniques are emerging for minimally invasive management. This section focuses on intraoperative pulmonary artery and vein injuries, major airway injuries and transections, injuries to major abdominal organs and effects of carbon dioxide insufflation during robotic pulmonary resection.